La représentation du corps dans la publicité - Méar, Annie (Anthropologica, 2022)
This paper reports a study of the portrayal of women in advertizing. A sample of automobile ads are analysed according to the dichotomic substitution/contiguity principles proposed by Jakobson for the study of child language and aphasia. The metaphoric and metonymic processes which are used to account for the topography of the messages lead to an elucidation of the sexual stereotypes that marketing decision groups maintain and reinforce through advertising. Our analysis shows that despite some superficial changes the roles attributed to women in ads remain basically unchanged.